Revisiting Sphere Sovereignty to Interpret Restrictions on Religious Freedom - Petri, Dennis P. (Philosophia reformata, 2015)
In this article, the Kuyperian concept of sphere sovereignty will be revisited in order to describe the multidimensionality of religious freedom. This article will show that true religious freedom requires not only a sovereign church sphere – the respect of church autonomy –, but also the freedom for religious expression in all other spheres of society. The first section will try to show that restrictions on religious expression in any sphere of society are restrictions on religious freedom. The second and third sections will provide examples of two global dynamics which in very distinct ways go against sphere sovereignty and specifically restrict religious expression in different spheres of society: “Islamic extremism” and “secular intolerance”. The article will conclude with a reflection about the virtues of sphere sovereignty as a guarantee against tyranny, and therefore also as a safeguard of religious freedom.